Genotypic variability of Pinus sylvestris L. on the drought-resistance attribute - E. Yu. Amineva; A. P. Gureev; T. M. Tabatskaya; O. S. Mashkina; V. N. Popov (Вавиловский журнал генетики и селекции)
There was an increase and intensification of droughts in connection with global climate change in recent decades. Not all plant organisms are able to adapt to changing environmental conditions. Therefore, the question of stressresistant (drought-resistant) genotypes selection for breeding is quite urgent. This problem also concerns forest tree plants, including Scots pine, which is one of the main foresters in the Voronezh region. The results of vegetative and generative sphere analysis of individual Scotch pine trees with the help of biotechnology, molecular-genetic and cytogenetic method are given in this study. The possibility of applying the tissue culture method in vitro for testing initial plants for stress resistance, including drought resistance, is explained by the interconnection of cells, tissues and the whole plant properties. It is shown that the cytogenetic characteristics of the seed progeny and the indicators of callusogenic reactions do not always coincide in different genotypes: in some cases energy resources are spent on ontogeny protection, while, in other cases, to reproductive function maintain. There are trees, in which the state the generative sphere in arid years is at the level of optimal years, and their callus cultures reaction remains unchanged even under simulated conditions of drought. Based on the results obtained for the selection of Scots pine drought-resistant genotypes we suggest applying a system of criteria characterizing both the ability of the vegetative sphere to survive in drought conditions on the basis of the tissue culture method in vitro (callus tissue formation speed, its viability, frequency of callusogenesis), and the state of the generative sphere with the help of cytogenetic analysis of seed progeny (frequency of mitosis pathologies, the proportion of cells with micronuclei, mitotic activity). The expediency of applying the biotechnological approach was proved by analysis of the gene expression level of stress proteins: the level of AbaH gene expression correlates greatly with the indicator of the viability of callus cultures, including ones on a nutrient medium with an additional stress agent (NaCl). Trees that can be assigned to drought-resistant ones, according to the results of the analysis, should be recommended for use in breeding.